Beneficiation study of the manganese ores of the Saidgi area, North Waziristan Agency, Pakistan - Khan, Azher; Shah, Mohammad Tahir; Ali, Liaqat; Mohammad , Wazir (Journal of Himalayan Earth Sciences, 2004)
Manganese is widely used in steel and chemical industries but its use in dyes, paint, battery cells, glass and textile industries is also of great importance. In Pakistan, millions of rupees are spent on the import of manganese di-oxide (MnO2) every month. Besides its extensive consumption in the steel industry, huge amount of MnO2 is imported for its use in battery cells, paints, glass and textile industries and poultry feed in Pakistan. Though manganese ores of various grades have been reported in Hazara, Kuram, Bajaur and North Waziristan agencies and Lasbela-Khuzdar, but their proper utilization is not made yet in the various mineral based industries of Pakistan. For this purpose, the manganese ores of Saidgi area of North Waziristan have been selected for their beneficiation or up-gradation during the present research work. These ores are of greater economic importance because of having inferred reserves of more than 34 thousand metric tons with MnO2 contents ranging from 36 to 60 wt%. Manganese ore required for the steel industry generally contains 48 wt% of MnO2. However, much higher grades ( 75 wt% MnO2) are required for battery making and chemical industries. The manganese ores of Saidgi area are having appropriate amount of MnO2 required for the steel industry but these ores need beneficiation or upgradation before being utilized in battery making and chemical industries. During the present study two different techniques (i.e., magnetic separation and gravity concentration methods) were used for the up-gradation of the Saidgi manganese ores. Two samples treated by magnetic separation method were up-graded from 37.98 wt % and 57.36 wt% to 79.1 wt% and 80.44 wt% of MnO2 respectively while two samples treated by gravity concentration were up-graded from 37.98 wt% and 57.36 to 60.23 wt% 72.19 of MnO2. It is, therefore, concluded that the Mn-deposits of Saidgi area can very easily. be up-graded by the method of magnetic separation for their use in the battery and chemical industries.